Natriuretic peptide dynamics with remote pulmonary artery pressure monitoring. (14th October 2021) - Casquete, D; Codina, P; Domingo, M; Santiago, E; Cediel, G; Spitaleri, G; Zamora, E; Santesmases, J; Boldo, M; Rivas, C; Gonzalez, B; Velayos, P; et al.
Abstract: Background: Real-life clinical practice has confirmed the value of pulmonary artery (PA) pressure-guided therapy in patients with heart failure (HF) and history of repeated HF hospitalizations (HFH), to greater extent to that reported in the pivotal clinical trial CHAMPION-HF. The value of hemodynamic monitoring in a population of patients with HF and elevated natriuretic peptides, but without recent HFH, is unknown. Objective: To assess N-terminal-pro-brain natriuretic peptide (NTproBNP) dynamics before and 6 months after PA pressure sensor implantation. Methods: Ten patients managed in a multidisciplinary HF clinic implanted with the CardioMEMS PA pressure sensor were consecutively included from June 2019 to July 2020. Mean age was 63.1±23.5 years, 30% were women, 40% had HF with reduced EF (EF <40%). NTproBNP was measured at baseline and six months after sensor implantation. Wilcoxon matched-pairs signed-rank test was used to compare NTproBNP values at baseline and at 6 months. Fractional polynomial fit plot was used to represent changes in mean PA pressure over time. Linear regression was used to predict the change in NTproBNP based on the change in PA pressures. Results: Mean daily pressure transmission rate was 92.4±5.1%. During the six-month study period 90% of patients had a change in medication related to PA pressure, with an average of 0.21 [0.17–0.66] changes per patient per month. Mean PA pressure at baseline was 28.5±9.5 mmHg, and decreased by 5.5 mmHg at 6 months (p=0.01) (Figure 1). NTproBNP was also significantly lower six months post CardioMEMS implantation; decreasing from 1696 pg/ml [976–2930] at baseline to 1046 pg/ml [616–2076] after six months (p=0.04) (Figure 2). There was a weak correlation between the change in NTproBNP and the change in mean PA pressure (R2=0.22, p=0.17). Conclusions: NTproBNP values were significantly lower 6-months following implantation of a PA pressure sensor to guide HF management. Mean PA pressures were also significantly reduced. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Hospital Universitari Germans Trias i Pujol